Expanding the change laboratory and the interventionist researcher's role in teacher education-school collaboration - Postholm, May Britt (Frontiers in Education, 2025)
This study is framed by cultural-historical activity theory (CHAT), and the Change Laboratory (CL) is used as a method to enhance development, with student teachers, teacher educators, and practice teachers as the participants. The aim of the project was to study and promote learning processes across the boundaries of school teaching and university-led teacher education; the purpose of the sub-study that this article is based on was to describe how the Change Laboratory and the role of the interventionist researcher (IR) expanded in a teacher education-school collaboration. The data material consists of the programs of each of the eight CL sessions that were conducted, and two dialogues are presented to provide a picture of the IR's role in dialogues during CL sessions. The findings show that the eight CL sessions are spread out over a period of 2 years, with 1 year in between, and that this temporal expansion establishes positive conditions for development in school and teacher education contexts, as well as in collaboration between these two institutions. Furthermore, the study highlights the importance of the IR listening to all perspectives to foster multivoicedness in CL sessions, thereby creating an arena characterized by trust and collective agency. The findings show that the IR is both a process leader and collaboration partner who provides direction and forceful input to the dialogues.